The working alliance in stuttering treatment: a neglected variable?. Issue 4 (13th March 2019) - Sønsterud, Hilda; Kirmess, Melanie; Howells, Kirsten; Ward, David; Feragen, Kristin Billaud; Halvorsen, Margrethe Seeger
Abstract: Background: Multiple factors can influence the working alliance and treatment outcome in speech and language therapy. The 'working alliance' is an important concept in treatment and can be described as the degree to which a treatment dyad is engaged in collaborative, purposive work. To date, relatively little attention has been paid to this concept within speech and language treatment in general, and within stuttering treatment research in particular. Aims: To investigate the role of the working alliance within stuttering treatment, and to evaluate whether the quality of the working alliance correlated with clients' concept of motivation and treatment outcomes 6 months post‐therapy. Methods & Procedures: Eighteen adults (21‐61 years) participated in this multiple single‐case treatment study, with treatment facilitated by an experienced speech and language therapist. The working alliance was investigated using the Working Alliance Inventory—Short Version Revised (WAI‐SR), an Extended version of the Client Preferences for Stuttering Treatment (CPST‐E), the Overall Assessment of Speakers' Experience of Stuttering—Adult version (OASES‐A), the Wright & Ayre Stuttering Self‐Rating Profile (WASSP) and the Hospital Anxiety and Depression Scale (HADS). Outcomes & Results: Analyses demonstrated significant associations between the working alliance and client motivation (r = 0.781) and treatment outcomes (r = 0.644) 6 months post‐treatment. The association between client‐led goals and therapy tasks appeared particularly important. Conclusions & Implications: : The working alliance between speech and language therapists and persons who stutter matters. Within the alliance, the level of client–clinician agreement on treatment goals and therapy tasks may be of greater importance than the bond between client and clinician. Further research with greater numbers of participants is warranted.